A RESEARCH ON THE PERFORMANCE DEGRADATION OF COMBINED ROTOR CONSIDERING CRACK IN DISK - SHAO ShiCong; WANG AiLun; LI ShuMin; ZHU ZhuoPing (Jixie qiangdu)
The performance degradation of combined rotor with crack of the disk is one of the significant reasons which cause malfunctions and accidents of gas turbine,while rules of performance degradation are still unclear. By using the finite element ANSYS platform to establish the combined rotor model,the dynamic analysis of the combined rotor with the crack in disk was conducted. The rules of performance degradation of combined rotor were obtained through defining degradation degree parameters. The rules of the performance degradation of combined rotor with crack in disk were verified experimentally. The results show that the performance degradation of combined rotor is extremely slow in the stable degradation stage,the significant transition point which leads to accidents occurs when the degradation reaches a certain extent. The different temperatures,rotation rate,ratios of crack depth to length and positions of the crack in disk have great influence on the degradation of combined rotor.